Evaluation on the use of tiles waste in stabilization of subgrade layer with rice husk ash as an activator agent / Nur Sabreena Marhami - Marhami, Nur Sabreena (2019)
Good design of highway gives a crucial contribution to economic growth and social benefit by providing access to employment, health and education services. In the process of designing the highway, the importance of having natural soil as subgrade layer is crucial to ensure the quality of road itself. One of the main and foremost processes in the construction of highway is subgrade soil stabilization. However, this process can be very costly. An alternative should be done in order to justify this problem. Therefore, in Malaysia, waste generation is increasing year by year due to the large amount of waste produced. As the world is now facing a serious problem on handling disposal materials, stabilizing agent for the soil can be used to solve this problem. Previous researches shown that tile waste is a potential source of construction material and soil stabilizer. Besides, many studies have been conducted with the aim of reducing the cost for soil stabilization; one option is by using waste materials such as tiles waste (TW) and rice husk ash (RHA) (Sumayya, et al., 2016). This type of wastes can improve the strength of the problematic soil thus make it to be environmentally friendly. The study is concerned with the role of TW content in stabilized problematic soil physical characteristics. The main aim of this research is to determine the optimum percentage of TW content for stabilization of problematic soil from Batu Kawan, Pulau Pinang. The soil was stabilized with five proportions of TW (15%, 20%, 25%, 30% and 35%) and constant RHA of 10% was used as an activator agent. The specimens were then cured for 0, 7 and 14 days before being subjected to the unconfined compression test (UCT). It was found that the optimum percentage of TW is at 30% added with RHA of 10% in soil. The highest value of UCT test for the sample was found to be 250kN/m2. Therefore, the test results showed that the RHA-TW admixture could effectively improve the strength of problematic soil.